Pembelajaran Pendidikan Agama Islam Dan Budi Pekerti Berbasis Higher Order Thinking Skills Dalam Meningkatkan Critical Thinking Dan Creative Thinking Siswa Di Smp Bustanul Makmur Banyuwangi - Ursula, Yordan Nafa (IJIT: Indonesian Journal of Islamic Teaching, 2025)
Higher Order Thinking Skills (HOTS) are now an important indicator of successful  learning in schools. All learning activities are directed toward helping students develop  strong higher-order thinking abilities, in line with the goals of 21st-century education. This study examined: (1) how HOTS-based Islamic Education learning improves the critical thinking of Grade IX students at SMP Bustanul Makmur Banyuwangi in the 2022/2023 academic year, and (2) how the same approach enhances their creative thinking skills. The research used a qualitative method with a case study design. Data were collected through observations, interviews, and documentation, using both primary and secondary sources. The data were analyzed using the Miles, Huberman, and Saldana interactive model, which includes data condensation, data display, and drawing conclusions. Data validity was ensured using triangulation of data, researchers, theory, and methods. The findings show that to improve critical thinking, lesson plans were designed to strengthen students’ skills in analysis, evaluation, and decision-making. Teachers used the Problem-Based Learning model along with discussion and presentation methods, and HOTS-based questions were used to measure students’ progress. Improvements were visible through assessment results and classroom activities, where students with strong critical thinking skills could use information more effectively to make appropriate decisions. To improve creative thinking, lesson plans focused on analysis, evaluation, and problem-solving. Teachers applied the Project-Based Learning model supported by group work. HOTS-based questions were also used to assess creative thinking. Students showed increased creativity through their project work and evaluations, as they became more capable of generating new ideas to solve the problems they encountered.